Analysis City Branding Lamongan Megilan as Marketing Communications of Region - Hidayatullah, Haqqi; Rajiyem, Rajiyem (Universitas Nusa Cendana, 2024)
The small number of tourists visiting Lamongan shows that the city's branding is not yet optimal. Based on data from Department of Tourism and Culture of Lamongan in 2020, there were 1,028,889 tourists visiting Lamongan, while the number of visitors to Gresik based on Gresik Open Data in 2020 was 2,103,355 people. One effort to increase the number of tourists is through optimizing city branding and currently Lamongan is developing the city branding